Gridded bathymetry from EM120 multibeam echosounder of R/V SONNE cruise SO174 (Gulf of Mexico) - dos Santos Ferreira, Christian; Wintersteller, Paul (PANGAEA, 2019)
Between 01.10.2003 and 12.11.2003, bathymetric data was acquired in the Gulf of Mexico during the R/V SONNE cruise SO174. The expedition was dedicated to the types and structures of near-surface marine methane hydrates and the environmental conditions required for their formation. Furthermore, the cruise aimed at the assessment of microbiological turnover and deployments of long-term observatories for examination of the mechanisms controlling the formation and dissociation of gas hydrate. Bathymetric mapping with the multibeam echosounder (MBES) SIMRAD EM120 was utilized to conduct high-quality seafloor maps in water depths between 500 and 1000 m, covering an area of 350 km² and notably improving the resolution of existing bathymetry. Sub-bottom profiling and plume imaging, visual seafloor observation, lander deployments, sediment coring, CT scanning and biological sampling complemented the research programme. CI Citation: Paul Wintersteller (seafloor-imaging@marum.de) as responsible party for bathymetry raw data ingest and approval. Description of the data source: During the SO174 cruise, the hull-mounted multibeam echosounder (MBES) SIMRAD EM120 was utilized to perform bathymetric mapping. It allows to conduct surveys in water depths of up to 11,000 m. Two transducer arrays transmit frequency coded acoustic signals (11.25 to 12.6 kHz). Data acquisition is based on successive emission-reception cycles of the signal. While the emission beam has a dimension of 150° across and 2° along track, the reception is obtained from 191 overlapping beams with widths of 2° across and 20° along track. The beam footprint has a dimension of 2° by 2°. The beam spacing can be set to equidistant or equiangular. For further information on the system, consult: https://www.km.kongsberg.com/ Depth is estimated from each beam by using the two-way travel time and the beam angle known from each beam, and taking into account the ray bending due to refraction in the water column by sound speed variations. Combining phase and amplitude is used to provide measurement accuracy practically independent of the beam pointing angle. A sound velocity for the calibration of the SIMRAD EM120 profile was obtained through a CTD cast. Responsible person during this cruise / PI: Gerhard Bohrmann (gbohrmann@marum.de) & Florian Meier (florian.meier@iwes.fraunhofer.de) Description of data processing: Postprocessing and products were conducted by the Seafloor-Imaging & Mapping group of MARUM/FB5, responsible person: Paul Wintersteller (seafloor-imaging@marum.de). The open source software MB-System suite (Caress, D.W., and D.N. Chayes, MB-System Version 5.5, open source software distributed from the MBARI and L-DEO web sites, 2000-2012.) was utilized for this purpose. The data was corrected for tide. There were no roll, pitch and heave corrections. Using Mbeditviz, artefacts were cleaned manually. NetCDF (GMT) grids of the edited data as well as statistics were created with mbgrid. The published bathymetric grid of the EM120 during cruise SO174 has a resolution of 35 m. No total propagated uncertainty (TPU) has been calculated to gather vertical or horizontal accuracy. A higher resolution is, at least partly, achievable. The grid extended with _num represents a raster dataset with the statistical number of beams/depths taken into account to create the depth of the cell. The extended _sd -grid contains the standard deviation for each cell. All grids produced are retrievable through the PANGAEA database (www.pangaea.de). Chief Scientist: Gerhard Bohrmann (gbohrmann@marum.de) CR: http://oceanrep.geomar.de/13539/1/GEOMAR_Rep_117_SO174.pdf CSR: https://www2.bsh.de/aktdat/dod/fahrtergebnis/2003/20040025.htm Raw data: https://doi.pangaea.de/10.1594/PANGAEA.902452
Keywords: Bathymetry; EM120; gas hydrates; Gulf of Mexico; hydroacoustics